Cold summer stream temperatures reduce recruitment of native cutthroat trout populations - Coleman, Mark Anthony, author; Fausch, Kurt D., advisor (Colorado State University. Libraries, 2007)
Translocation is a key strategy for conserving subspecies of native cutthroat trout Oncorhynchus clarkii, which have declined markedly throughout their native ranges in North America. Previous research showed that translocation success in high-elevation southern Rocky Mountain streams was more likely in warmer streams, and suggested that cold temperatures could limit juvenile trout recruitment and explain translocation failures. However, the effects of cold temperature on recruitment had not been previously investigated. I studied these effects using an integrated laboratory and field approach. In the lab, age-0 Colorado River cutthroat trout O. c. pleuriticus were subjected to one of three natural temperature regimes during two years, which averaged 7°C, 8.5°C and 10.0°C during the warmest summer month. From hatching to swimup, mean survival was high during both years, ranging from 97% (warm regime) to 85% (cold). After swimup, warm regime fry had much greater survival and grew more than 60% larger, on average, than cold regime fry by the onset of winter in the 2003 experiment. The pattern of lower survival in colder temperature regimes held through mid-winter, with 76% survival (warm regime), 62% (intermediate), and 29% (cold). Likewise, during the 2004 experiment, survival to early winter ranged from 44% (warm regime) to 10% (cold). Most mortality in all treatments occurred during a recruitment bottleneck encompassing a 4- to 6-week period following swimup. A response surface analysis of percent dry weight data indicated that the energy content of fry at swimup was lower in colder regimes, and declined during the recruitment bottleneck in all regimes. In the field, I monitored temperatures and conducted surveys to estimate densities of age-0 fry at peak emergence in six headwater streams that varied in thermal characteristics. Density and growth increased with Celsius degree days during the growing season. My results indicate a strong recruitment bottleneck after swimup, when temperature-related energy deficits probably cause significant mortality. Fisheries managers in the southern Rocky Mountains may increase translocation success of native cutthroat trout by selecting sites with ≥800-900 degree days during the growing season, and fry grow to ≥30-35 mm by the end of the growing season.
Keywords: cutthroat trout; Oncorhynchus clarkii; recruitment; ecology; aquaculture; fish production; aquatic sciences